Aberrantly Methylated-Differentially Expressed Genes Identify Novel Atherosclerosis Risk Subtypes - Xue, Yuzhou; Guo, Yongzheng; Luo, Suxin; Zhou, Wei; Xiang, Jing; Zhu, Yuansong; Xiang, Zhenxian; Shen, Jian (Frontiers in Genetics, 2020)
Increasing evidence has indicated that modulation of epigenetic mechanisms, especially methylation and long-noncoding RNA (lncRNA) regulation, play a pivotal role in the process of atherosclerosis; however, few studies focused on revealing the epigenetic-related subgroups during atherosclerotic progression using unsupervised clustering analysis. Hence, we aimed to identify the epigenetics related differentially-expressed genes associated with atherosclerosis subtypes and characterize clinical utility in atherosclerosis. Eighty samples with expression data (GSE40231) and forty-nine samples with methylation data (GSE46394) from large artery plaque were downloaded from the GEO database and aberrantly methylated-differentially expressed (AMDE) genes were identified based on the relationship between methylation and expression. Furthermore, we conducted weighted correlation network analysis (WGCNA) and co-expression analysis to identify the core AMDE genes strongly involved in atherosclerosis. K-means clustering was used to characterized two subtypes of atherosclerosis in GSE40231 and then twenty-nine samples was recognized as validation dataset (GSE28829). In blood sample cohort (GSE90074), Chi-square test and logistic analysis were performed to explore the clinical implication of the K-means clusters. Furthermore, Significance Analysis of Microarrays and Prediction Analysis of Microarrays (PAM) were applied to identify the signature AMDE genes. Moreover, the classification performance of signature AMDE genes-based classifier from PAM was validated in another blood sample cohort (GSE34822). A total of 1569 AMDE mRNAs and eight AMDE long non-coding RNAs (lncRNAs) were identified by differential analysis. Through the WGCNA and co-expression analysis, 32 AMDE mRNAs and seven AMDE lncRNAs were identified as the core genes involved in atherosclerosis development. Functional analysis revealed that AMDE genes were strongly related to inflammation and axon guidance. In the clinical analysis, the atherosclerotic subtypes were associated with the severity of coronary artery disease and risk of adverse events. Eight genes, including PARP15, SERGEF, PDGFD, MRPL45, UBR1, STAU1, WIZ, and LSM4, were selected as the signature AMDE genes, that most significantly differentiated between atherosclerotic subtypes. Ultimately, the area under curve (AUC) of signature AMDE genes-based classifier for atherosclerotic subtypes were 0.858 and 0.812 in GSE90074 and GSE34822, respectively. This study identified the AMDE genes (lncRNAs and mRNAs) that could be implemented in clinical clustering to recognize high risk atherosclerotic patients.